The adaptation triangle: a multivariate analysis of vulnerability, resilience and livelihood strategies in semi-arid regions of India - Mannepalli, Bharath Kumar; Kushwaha, Saket; Kamalvanshi, Virendra; Parida, Pradip Kumar; Kemboi, Evans; Yadav, Ankit; Deep, Prakhar; Mukherjee, Reshmi (Frontiers in Climate, 2025)
India’s semi-arid regions covering 37% of is geographical area were among the most climate-vulnerable ecosystems globally characterized by erratic rainfall, intense heat and fragile livelihoods. Despite extensive research, few studies have comprehensively investigated household vulnerability, resilience and their interplay in these dry regions. This study formulates the “adaptation triangle” framework to examine the interlinkages among livelihood strategies, vulnerability and resilience. Employing a multistage stratified random sampling methodology, primary data was collected from 375 households in Rajasthan, Telangana and Tamil Nadu, encompassing 69 socioeconomic, environmental and institutional factors. Composite indices for household livelihood vulnerability (HLVI) and resilience (HRI) were constructed in accordance with IPCC and FAO guidelines. Multivariate linear regression was employed to investigate the influence of 13 livelihood strategies on HLVI and HRI, while multinomial logistic regression evaluated their effect on household transitions within the vulnerability-resilience matrix’s four quadrants. National-level data indicates moderate vulnerability (HLVI = 0.517) and low resilience (HRI = 0.489) with 37.07% of households categorized in the most at-risk high vulnerability-low resilience (HVLR) quadrant. Key adaptive strategies such as income diversification, rainwater harvesting, adjusting sowing dates and adoption of crop and livestock insurance were found to substantially reduce vulnerability and enhance resilience. Households dependent on casual labor face heightened climate risk was also found to be significant. This study reinforces that livelihood choices are not only survival responses but pivotal levers in shaping climate adaptation outcomes. Policy recommendations include promoting diversified and climate-resilient livelihoods, expanding social safety nets, scaling up insurance access, microfinances and investing in water harvesting and agro-ecological infrastructure. The adaptation triangle framework provides a valuable lens to inform targeted interventions and build long-term resilience among vulnerable populations in India’s semi-arid regions.